The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1413-35552007000400005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das atividades de vida diária de idosos com diferentes níveis de demência

Abstract: Objective: To compare the performance of elderly people with different levels of severity of dementia using questionnaires on basic activities of daily living (BADLs) and instrumental activities of daily living (IADLs). Also, to verify whether there were any association between the IADL questionnaires applied. Method: Ninety elderly people, aged 75.46 ± 7.66 years with a clinical diagnosis of dementia (DSM-IV/APA) who were seen at the Minas Gerais Reference Center for the Elderly, were randomized selected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
27

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 21 publications
1
16
0
27
Order By: Relevance
“…1,2 Currently, close to 44 million people live with this disease. 3 Alzheimer´s disease (AD) is the most common cause of this illness, causing between 60 and 70% of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Currently, close to 44 million people live with this disease. 3 Alzheimer´s disease (AD) is the most common cause of this illness, causing between 60 and 70% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…3 Alzheimer´s disease (AD) is the most common cause of this illness, causing between 60 and 70% of cases. 1,2 Between normal aging and dementia, there is a period known as mild cognitive impairment (MCI). This period is characterized by the maintenance of independence, from a functional perspective, and cognitive loss, when compared to normal people, without attaining the criteria of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that changes in ADL performance can occur at the initial stages of the disease. It has been suggested that there is a relationship between the severity of cognitive impairments and the functional performance; initially the losses are observed in IADLs and basic ADLs are only damaged in more advanced stages of dementia 10 . Based on the statistical analysis observed in the results, the items of the new instrument (ADLQ-Brazilian version) were distributed into six domains, encompassing relevant basic and instrumental ADLs usually affected during the process of the disease, which are important to the functional assessment 7 .…”
Section: Construct Validitymentioning
confidence: 99%
“…Although the concept of functional capacity is quite complex and encompasses deficiency, incapacity, disadvantage, as well as autonomy and independence, in practice, we work with the concept of capacity/incapacity 10 . Functional incapacity is defined by difficulty while performing certain gestures and ADLs or even the impossibility of performing these activities 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation